An Economy Orientated Towards the Reproduction of Life - Hinkelammert, Franz; Mora Jiménez, Henry (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2009)
This article explores the need for and possibility of constructing a rationality that transcends –without necessarily eliminating– the instrumental rationality. This rationality is not based on the preferences of the consumer, but on people’s needs; not on economic calculations but on the ethics of the common good that enable the conservation and reproduction of the natural cycle of human and natural life. This article suggests that in order to attain this rationality, a criticism of the logic of empirical fetishism is necessary; so too, is a critique of our understanding of reality constituted entirely by market relations. This requires an answer to one critical question: what kind of society do we really want?